The Feasibility Study of Internet-Assisted Play Therapy to Resolve Psychological Disorders in Primary Healthcare Settings: A Qualitative Study - SHABANI, SEVİL MOMENİ; Darabi, Fatemeh; Nejaddadgar, Nazila; Azimi, Ahad; Shabani, Masoud (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Play therapy is an intelligent tool in cognitive-behavioral therapies. In today's world, the Internet and technology play a key role in all aspects of people's life including mental health. The present study explores the feasibility of using Internet-assisted play therapy to solve children's psychological issues in primary healthcare systems. MATERIALS AND METHODS: The present qualitative research was conducted by the content analysis approach on 20 experts working in the healthcare centers, who were selected purposefully. The sample was saturated with these 20 participants. Data were collected through semi-structured interviews and were coded manually. Then, they were analyzed in the Atlas.ti software package. RESULTS: The results revealed 15 themes and 10 sub-themes. The themes included (1) safety, (2) efficiency, (3) client-orientedness, (4) organizational growth, (5) time, (6) effectiveness, (7) justice-orientedness, (8) access, (9) feedback, (10) analysis, (11) children's computer game room, (12) reward, (13) group game, and (14) capability to be integrated into other electronic programs. CONCLUSION: It seems that Internet-based play therapy is plausible to be used as a service in primary healthcare to tackle the psychological problems of children in the target population if the challenges related to the exploratory themes are taken care of.
Keywords: Cognitive Behavior Therapy; Internet; Mental Health; Play Therapy